Baked flux for submerged arc welding of high strength steel and submerged arc welding method

By using reasonably prepared calcined flux and appropriate element fire welding wires in immersion arc welding of high-strength steel, the problem of insufficient strength and toughness of weld metal under large heat input is solved, and the high strength, high toughness and low hydrogen content of the weld parts are achieved, reducing the risk of cracks in the welding heat-affected zone.

JP2025058858AActive Publication Date: 2025-04-09JFE STEEL CORP +1
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2024063731
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-28
Filing Date
2024-04-11
Publication Date
2025-04-09
Estimated Expiration
2044-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to achieve sufficient strength and toughness of weld metal in high-strength steels of 780 MPa or higher by immersion arc welding with large heat input, and there is a problem that cracks may occur in the welding heat-affected zone.

Method used

The appropriate fire wire and flux formula is used to contain appropriate amounts of Ni, Cr, Mo, V, Nb and other elements, and the proportion of components such as SiO2, CaO, MgO, Al2O3 is controlled through the reasonable formulation of calcined flux to ensure that the welding parts have low diffusible hydrogen content, no defects, strength and toughness comparable to the substrate at high heat input (100 kJ/cm or higher) during welding.

Benefits of technology

Immersion arc welding of 780 MPa or higher strength steel under high heat input conditions ensures high strength and high toughness of weld metal, reduces the risk of cracks in the welding heat-affected zone, and improves the feasibility and efficiency of welding work.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058858000001_ABST
    Figure 2025058858000001_ABST
Patent Text Reader

Abstract

To provide a flux and a welding method for securing weld metal having strength and tenacity comparable to those of a base material at a high heat input submerged arc joint of high strength steel.SOLUTION: A baked flux contains SiO2:15-25%, CaO:3-15%, MgO:25-45%, Al2O3:5-20%, CaF2:5-20%, a total of 0.5-10.0% of one or two kinds of Na2O and K2O, a total of 3-8% of the CO2 conversion values of one or two kinds of CaCO3 and MgCO3, Ni:3.00-7.20%, Cr:0.90-2.40%, Mo:0.50-1.30%, and a total of 0.080-0.220% of one or two kinds of V and Nb.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sintered flux for submerged arc welding of high tensile steel and a submerged arc welding method, and in particular to a technology for welding high-strength, extra-thick steel with a strength of 780 MPa or more by multi-layer welding of 100 kJ / cm or more, and for ensuring that the weld metal has a low amount of diffusible hydrogen and has strength and toughness equivalent to that of the base metal. [Background technology]

[0002] In recent years, as high-rise buildings have become larger and spans between columns have become longer, box columns made of extra-thick high-tensile steel have come to be used. Submerged arc welding, which requires a large heat input and allows for highly efficient welding, is widely used for welding box column corner joints.

[0003] Fluxes used in submerged arc welding are roughly divided into molten type and sintered type according to their manufacturing method. The former is a glassy flux made by mixing raw materials in a specified composition, melting it in an arc furnace, etc., solidifying it, and then pulverizing it to an appropriate particle size. The latter is made by mixing raw material powder and alloy elements in a specified composition, granulating it with, for example, sodium silicate as a binder, and sintering it.

[0004] In submerged arc welding of box column corner joints, it is common to use a sintered flux with a relatively high basicity in order to obtain a weld metal with high strength and toughness. In addition, when welding with a welding heat input (hereinafter simply referred to as "heat input") in the range of 300 to 600 kJ / cm, a sintered flux containing iron powder is used, and when one-sided multi-layer welding is performed with a heat input of 300 kJ / cm or less, iron powder is often not added.

[0005] In the case of sintered flux containing iron powder, the sintering temperature must be relatively low to prevent oxidation of the iron powder during manufacturing, and the inability to sinter at high temperatures is the fundamental reason why the moisture content in the flux cannot be reduced. In particular, when welding extremely thick box columns, where one-pass welding is difficult due to the capacity of the welding machine and the characteristics of the joints, and multi-layer welding is applied, there is a problem that the cooling rate after welding is high and there is no time to release hydrogen in the weld metal, so it remains. On the other hand, when a flux with a high moisture content is used, cracks due to diffusible hydrogen are likely to occur in the heat-affected zone of welding, and this tendency is known to be more pronounced in high-tensile steels with increased alloy additions.

[0006] Sintered fluxes without iron powder can be sintered at a higher temperature than those with iron powder, which allows for a reduction in moisture content. In addition, in order to ensure the strength and toughness of the weld metal equivalent to that of the base material, sintered fluxes that allow the composition of the weld metal to be freely adjusted are used in the submerged arc welding of high-tensile steels, and various technical developments have been carried out.

[0007] For example, Patent Document 1 specifies the composition of sintered flux and welding wire, and describes the following for 80 kg class high tensile steel: V E -80 The paper describes a technology for obtaining weld metal with a toughness of 3.5 kgf m or more. V E -80 "℃" refers to the Charpy absorbed energy at the test temperature indicated by the subscript on the right (-80℃ in this example) (the same applies below). Note that the welding wire will be simply referred to as "wire" hereinafter.

[0008] In Patent Document 2, the composition of the sintered flux and wire is specified, and the tensile strength is 780 MPa or more, V E -60 A technique is described for obtaining a weld metal having a toughness of 69 J or more at 1000 K.

[0009] Patent Document 3 describes a sinterable flux for high-strength steel that can obtain a weld metal with good toughness even at a high strength of 780 MPa class.

[0010] Patent Document 4 describes a technology in which the composition of the weld metal is optimized by combining a solid wire and a sintered flux, thereby obtaining strength and stable toughness of the weld metal, eliminating welding defects, and improving welding workability.

[0011] Patent Document 5 relates to submerged arc welding of 780 MPa-class high-tensile steel and describes a technique for obtaining a weld metal having high toughness and good strength by using a combination of a sintered flux and a wire.

[0012] Patent Document 6 describes a technique for submerged arc welding of 780 MPa-class high-tensile steel, in which a sintered flux with limited alloy element content and optimized flux grain size is combined with a solid wire with limited components, aiming to obtain a weld metal with good bead shape free of welding defects, ease of welding work, and excellent mechanical performance.

[0013] Patent Document 7 describes a technology for submerged arc welding of high-tensile steel, in which a high-strength welding wire is used and appropriate amounts of Si and Mn are included in the flux, thereby ensuring high strength while also promoting deoxidation in the weld metal by including appropriate amounts of Al, MgO, and CaF2, thereby improving toughness, reducing the amount of diffusible hydrogen, stabilizing the arc, improving slag removability, and improving the bead appearance and shape. [Prior art documents] [Patent documents]

[0014] [Patent Document 1] Japanese Patent Application Publication No. 3-52796 [Patent Document 2] JP 2013-39604 A [Patent Document 3] Japanese Patent Application Publication No. 6-328291 [Patent Document 4] JP 2007-260696 A [Patent Document 5] Japanese Patent Application Publication No. 5-212583 [Patent Document 6] JP 2015-120175 A [Patent Document 7] JP 2020-131221 A Summary of the Invention [Problem to be solved by the invention]

[0015] The conventional techniques described in Patent Documents 1 to 7 aim to improve the mechanical properties of welds, such as the strength and toughness of the weld metal obtained by submerged arc welding. However, the mechanical properties of the welds obtained by these conventional techniques are the result of applying a heat input range of 24 to 36 kJ / cm (examples in Patent Documents 1 to 7), which is less than 100 kJ / cm. The conventional techniques do not take into consideration the application of high heat input submerged arc welding of 100 kJ / cm or more to high tensile steel of 780 MPa or more.

[0016] The present invention has been made in view of the above problems, and has the following object. That is, to provide a sinterable flux that can be used to perform high heat input welding of 100 kJ / cm or more on a high tensile steel base material having a tensile strength of 780 MPa or more, and can efficiently obtain a weld with good workability and sufficient strength and toughness equivalent to that of a base material with a low diffusible hydrogen content and no defects. Another object of the present invention is to provide a submerged arc welding method that combines the sinterable flux with a welding wire to ensure even greater strength and toughness in the weld metal. [Means for solving the problem]

[0017] The present inventors have conducted extensive research into the chemical compositions of sinterable fluxes for submerged arc welding that can solve the above problems and the chemical compositions of welding wires to be combined with these sinterable fluxes.

[0018] As a result, by adding appropriate amounts of Ni, Cr, Mo, V, and Nb to the sintered flux, the weld metal of multi-layer welding with a heat input of 100 kJ / cm or more has a high strength of 780 MPa or more and V Excellent toughness of over 100J was ensured at E0℃.

[0019] In addition, the amount of diffusible hydrogen in the weld metal was reduced by a synergistic effect of setting the CO2 equivalent value from CaCO3 and / or MgCO3 in the flux within an appropriate range.

[0020] Furthermore, the welding workability of these materials is improved by optimizing the amount of Na2O and K2O for arc stability, by optimizing the amount of SiO2, Al2O3 and CaO for bead appearance and bead shape, and by including appropriate amounts of Al2O3 and SiO2 for slag removability.

[0021] Furthermore, it has been discovered that by combining a specific high strength welding wire, better strength and toughness can be obtained in the weld metal.

[0022] The present invention was made based on these findings and through further investigation, and the gist of the present invention is as follows. [1] A sinterable flux for submerged arc welding of high tensile steel, comprising: The chemical composition of the sintered flux is, in mass%, SiO2: 15-25%, CaO: 3-15%, MgO: 25-45%, Al2O3: 5-20%, CaF2: 5-20%, Sum of one or both of Na2O and K2O: 0.5 to 10.0%, Sum of CO2 equivalent values ​​of one or both of CaCO3 and MgCO3: 3-8%; Ni: 3.00~7.20%, Cr: 0.90~2.40%, Mo: 0.50-1.30%, V and Nb: 0.080 to 0.220% in total; The balance is composed of Fe from iron alloys and unavoidable impurities. A baked flux for submerged arc welding of high tensile steels, characterized in that [2] In the above [1], in addition to the chemical composition of the sintered flux, the flux further contains, by mass%, one or more selected from Si, Mn, Al, Ti and Mg: 0.6 to 3.0% in total. A baked flux for submerged arc welding of high tensile steels, characterized in that [3] The sinterable flux for submerged arc welding of high tensile steel according to [1] or [2] above, characterized in that the high tensile steel has a tensile strength of 780 MPa or more. [4] A method for submerged arc welding of high tensile steel, comprising the steps of: combining the sintered flux according to [1] or [2] with a welding wire; The chemical composition of the welding wire is, in mass%, C: 0.05-0.12%, Si: 0.01 to 0.35%, Mn: 1.30-2.10%, Cu: 0.01-0.25%, Ni: 0.70-3.20%, Mo: 0.40-0.90%, Sum of one or both of V and Nb: 0.001 to 0.070%, P: 0.015% or less, S: 0.015% or less, Ceq represented by the following formula (1) is 0.40 to 0.80%, The balance consists of Fe and unavoidable impurities. A method for submerged arc welding of high tensile steel. Ceq=C+Si / 24+Mn / 6+Ni / 40+Cr / 5+Mo / 4+V / 14...(1) In formula (1), C, Si, Mn, Ni, Cr, Mo, and V are the contents (mass%) of each element, and the content of an element that is not contained is 0 (zero). [5] In the above [4], in addition to the chemical composition of the welding wire, Contains one or more selected from Cr: 0.01-0.10%, Ti: 0.001-0.050%, and Al: 0.001-0.050%. A method for submerged arc welding of high tensile steel. [6] The method for submerged arc welding of high tensile steel according to [4] or [5] above, characterized in that the high tensile steel is a high tensile steel having a tensile strength of 780 MPa or more. [7] The method for submerged arc welding of high tensile steel according to any one of the above [4] to [6], characterized in that the welding heat input is 100 kJ / cm or more. [8] A method for submerged arc welding of high tensile steel according to any one of the above [4] to [7], characterized in that the welding method is performed by multi-pass welding. Effect of the Invention

[0023] The sintered flux according to the present invention has the following effects in submerged arc welding of high tensile steel having a tensile strength of 780 MPa or more. That is, it has the effect of efficiently obtaining a welded joint having a low amount of diffusible hydrogen, no defects, and strength and toughness equivalent to that of the base metal by multi-layer welding with a heat input of 100 kJ / cm or more with good workability. Furthermore, the submerged arc welding method according to the present invention has the effect of ensuring a weld metal having high strength and toughness. [Brief description of the drawings]

[0024] [Figure 1] FIG. 2 is a schematic diagram showing a welding procedure for a welding test in the examples. [Diagram 2] FIG. 2 is a schematic diagram showing an electrode arrangement in an embodiment. [Diagram 3] FIG. 2 is a schematic diagram showing a cross section of a welded joint and the arrangement of a vertical flaw detector in an embodiment. [Figure 4] FIG. 2 is a schematic diagram showing positions at which tensile test specimens were taken from the weld metal. [Diagram 5] FIG. 2 is a schematic diagram showing positions at which Charpy test pieces were taken from the weld metal. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention is applied to submerged arc welding in which high tensile steel is used as a base metal.

[0026] [Base material] In particular, it is preferable that the base metal has a tensile strength of 780 MPa or more. If the base metal has a tensile strength of 780 MPa or more, the weld metal of a submerged arc welded joint in the base metal strength range and heat input range (100 kJ / cm or more) not considered in the conventional technology can be ensured to have strength and toughness equivalent to that of the base metal. On the other hand, if the base metal has a tensile strength of less than 780 MPa, the strength and toughness of the weld metal can be ensured by the conventional technology.

[0027] In order to solve the above problems, the present invention limits the chemical composition of the sinterable flux and further limits the chemical composition of the welding wire. Here, the content in each of the chemical compositions of the sinterable flux and the welding wire is expressed simply as "%" in units of "mass%".

[0028] [Chemical composition of fired flux] First, the chemical composition of the sintered flux according to the present invention and the reasons for setting the range of the composition will be described.

[0029] [SiO2: 15-25%] SiO2 is a slag generating agent, and is an important component for adjusting basicity and viscosity and obtaining good weld metal toughness and weld bead formation. SiO2 also has the effect of making the slag vitreous and friable, and improving slag removability. If SiO2 is less than 15%, the viscosity of the slag decreases and the bead shape becomes poor. On the other hand, if SiO2 exceeds 25%, the amount of oxygen in the weld metal increases, which reduces toughness and deteriorates slag removability. Therefore, SiO2 is set to 15 to 25%. Preferably, it is 16 to 22%.

[0030] [CaO: 3-15%] CaO is an important component for adjusting the basicity and softening point of the slag. If the CaO content is less than 3%, almost no transverse cracks occur in the solidified slag, and the slag removability deteriorates. On the other hand, if the CaO content exceeds 15%, the slag fluidity is poor, the bead height becomes non-uniform, and the bead shape and slag removability become poor. Therefore, the CaO content is set to 3 to 15%, and preferably 5 to 13%. Note that CaO includes the CaO content of CaCO3.

[0031] [MgO: 25~45%] MgO is a necessary component from the viewpoints of adjusting the basicity and softening point of the slag and ensuring the removability of the slag. If the MgO content is less than 25%, the removability of the slag in the groove is significantly deteriorated, the bead becomes rough, and pockmarks are likely to occur. On the other hand, if the MgO content exceeds 45%, the bead shape becomes convex and the bead width becomes narrow, and defects such as poor fusion and slag entrapment are likely to occur, so the MgO content is set to 25 to 45%, and preferably 27 to 40%. Note that MgO includes the MgO content of MgCO3.

[0032] [Al2O3: 5-20%] Al2O3 is a component necessary for adjusting the softening point and viscosity of the slag, and also has the effect of stabilizing the arc. If Al2O3 is less than 5%, the arc becomes unstable, the bead becomes rough, and the bead appearance and slag removability become poor. On the other hand, if Al2O3 exceeds 20%, the bead becomes convex, the bead shape becomes poor, and the slag removability also becomes poor. Furthermore, if Al2O3 exceeds 20%, welding defects such as slag inclusion are likely to occur. Therefore, Al2O3 is set to 5 to 20%, and preferably 7 to 18%.

[0033] [CaF2: 5-20%] CaF2 is a component necessary for adjusting the basicity and viscosity of the slag. If the CaF2 content is less than 5%, the basicity will be low and the fluidity of the slag will be insufficient, resulting in a narrow bead width. On the other hand, if the CaF2 content exceeds 20%, the arc will become unstable and welding defects will be more likely to occur. Therefore, the CaF2 content is set to 5 to 20%. Preferably, it is set to 7 to 18%.

[0034] [Total of one or both of Na2O and K2O: 0.5-10.0%] Na2O and K2O, whose main raw materials are water glass (sodium silicate, potassium silicate), have the effect of stabilizing the arc. If the total of one or both of Na2O and K2O is less than 0.5%, the arc becomes unstable. On the other hand, if the total of one or both of Na2O and K2O exceeds 10.0%, the fluidity of the slag becomes too high, the bead appearance deteriorates, and pockmarks tend to occur. Therefore, the total of one or both of Na2O and K2O is set to 0.5 to 10.0%, and preferably 1.5 to 9.0%.

[0035] [Total of CO2 equivalent value of one or both of CaCO3 and MgCO3: 3~8%] CaCO3 and MgCO3 have the effect of lowering the nitrogen partial pressure in the arc atmosphere and reducing the nitrogen content of the weld metal, and further reducing the diffusible hydrogen content of the weld metal. Here, if the total of the CO2 equivalent values ​​of one or two of CaCO3 and MgCO3 is less than 3%, the nitrogen content in the weld metal increases, the toughness of the weld metal decreases, and the diffusible hydrogen content of the weld metal increases, increasing the low-temperature cracking susceptibility. On the other hand, if the total of the CO2 equivalent values ​​of one or two of CaCO3 and MgCO3 exceeds 8%, pockmarks and pits are likely to occur on the bead surface, resulting in poor bead appearance, and the oxygen content in the weld metal increases, decreasing the toughness. Therefore, the total of the CO2 equivalent values ​​of one or two of CaCO3 and MgCO3 is 3 to 8%. Preferably, it is 4 to 7%. In addition, when only one of CaCO3 and MgCO3 is contained, the CO2 equivalent value of that one type is the "total".

[0036] [Ni:3.00~7.20%] Ni is an element intended to ensure the strength and toughness of the weld metal. If Ni is less than 3.00%, the strength and toughness of the weld metal are reduced. On the other hand, if Ni exceeds 7.20%, the austenite grain size of the weld metal becomes coarse, reducing the toughness. Therefore, Ni is set to 3.00 to 7.20%, and preferably 3.50 to 6.50%. For Ni, for example, metallic Ni and Fe-Ni can be used as a raw material.

[0037] [Cr:0.90~2.40%] Cr has the effect of ensuring the strength of the weld metal and stabilizing the toughness. If the Cr content is less than 0.90%, stable toughness cannot be obtained. On the other hand, if the Cr content exceeds 2.40%, the strength of the weld metal becomes excessive and the toughness deteriorates. Therefore, the Cr content is set to 0.90 to 2.40%, and preferably 1.10 to 2.00%. For Cr, for example, metallic Cr and Fe-Cr can be used as a raw material.

[0038] [Mo: 0.50~1.30%] Mo is an element intended to ensure the strength of the weld metal. If Mo is less than 0.50%, the strength of the weld metal is reduced. On the other hand, if Mo exceeds 1.30%, the weld metal is significantly hardened and the toughness is reduced. Therefore, Mo is set to 0.50 to 1.30%, and preferably 0.60 to 1.10%. Note that, for example, metallic Mo and Fe-Mo can be used as the raw material for Mo.

[0039] [Total of one or both of V and Nb: 0.080~0.220%] V and Nb are elements intended to ensure the strength of the weld metal. If the total of one or both of V and Nb is less than 0.080%, the strength is insufficient. On the other hand, if the total of one or both of V and Nb exceeds 0.220%, the strength becomes too high and the toughness decreases. Therefore, the total of one or both of V and Nb is set to 0.080 to 0.220%. Preferably, it is 0.085 to 0.150%. Note that metal V, metal Nb, Fe-V, Fe-Nb, Fe-V-Nb, etc. can be used as the raw material for one or both of V and Nb.

[0040] [Si, Mn, Al, Ti, Mg: 0.6-3.0%] Furthermore, it is preferable to add one or more elements selected from the optional compositions of Si, Mn, Al, Ti, and Mg as necessary. These elements have a deoxidizing effect. That is, when the amount of oxygen in the weld metal increases, the low-temperature toughness such as the Charpy impact value and the CTOD value deteriorates. Therefore, Si, Mn, Al, Ti, or Mg is necessary as a deoxidizing agent. If the total amount of one or more selected from these is less than 0.6%, the deoxidizing effect is insufficient and the low-temperature toughness such as the Charpy impact value and the CTOD value decreases. On the other hand, if it exceeds 3.0%, the amount of oxygen in the weld metal decreases, but if these elements are excessively contained in the weld metal, it will cause a decrease in the low-temperature toughness such as the Charpy impact value and the CTOD value. Therefore, it is preferable that the total amount of one or more selected from Si, Mn, Al, Ti, and Mg is 0.6 to 3.0%. More preferably, it is 0.9 to 2.8%.

[0041] The forms of these elements added to the flux are as follows: Si can be in the form of metal Si, Fe-Si, Ca-Si, etc. Similarly, Mn can be in the form of metal Mn, Fe-Mn, Al can be in the form of metal Al, Fe-Al, Al-Mg, Ti can be in the form of metal Ti, and Mg can be in the form of metal Mg, etc.

[0042] [Remaining composition] The balance in the sintered flux is Fe from iron alloys such as Fe-Mn, Fe-Al, Fe-Ni, Fe-Cr, Fe-Mo, Fe-V, Fe-Nb, and Fe-V-Nb, and inevitable impurities. The inevitable impurities are MnO, FeO, BO, C, P, S, etc., and among them, P and S are preferably as low as possible because they both form compounds with low melting points and reduce the toughness of the weld metal. The sintered flux does not contain iron powder, which allows the sintering temperature to be set at 400 to 650° C. and reduces the moisture content.

[0043] [Method of manufacturing fired flux] Next, a method for producing the sintered flux will be described. The flux raw material powder is mixed so as to have the above-mentioned chemical composition, kneaded with a binder, granulated, and fired. The granulation method is not particularly limited, but it is preferable to use a rolling granulator, an extrusion granulator, or the like. After granulation, it is preferable to carry out a granulation process such as removing dust and crushing coarse particles to make the particle diameter 2.5 mm or less. As the binder, an aqueous solution of polyvinyl alcohol or water glass is preferable. Among them, sodium silicate (water glass) with a molar ratio of SiO2 and Na2O of 1 to 5, which has been used conventionally, is sufficient. The amount of the binder used is preferably about 100 to 300 cc per kg of the flux raw material. The firing after granulation is preferably carried out at a temperature of 400 to 650°C. This is because if the firing temperature is less than 400°C, the moisture brought in from the binder is not sufficiently dried, which leads to an increase in diffusible hydrogen in the weld metal. On the other hand, if the firing temperature exceeds 650°C, the carbonate in the flux decomposes, and the shielding effect of CO2 cannot be obtained. Firing is carried out using a rotary kiln, a stationary batch furnace, a belt-type firing furnace, etc.

[0044] [Chemical composition of welding wire] Next, the chemical composition of the welding wire preferably used in the submerged arc welding method of the present invention and the reasons for setting the range of the composition will be described.

[0045] [C: 0.05~0.12%] C is an important element that ensures the strength of the weld metal through solid solution strengthening, and also has the effect of reducing the amount of oxygen in the arc atmosphere and the weld metal by reacting with oxygen in the arc. If C is less than 0.05%, the effects of deoxidization and ensuring strength are insufficient, and toughness is also reduced. On the other hand, if C exceeds 0.12%, the weld metal becomes a structure mainly composed of martensite, which increases the strength but reduces the toughness. In addition, hot cracking is likely to occur. Therefore, C is set to 0.05 to 0.12%, and preferably 0.06 to 0.11%.

[0046] [Si: 0.01~0.35%] Silicon has the effect of reducing the oxygen content in the weld metal and is an important element for improving toughness. If the silicon content is less than 0.01%, the toughness of the weld metal decreases. On the other hand, if the silicon content exceeds 0.35%, the matrix of the weld metal is solid-solution strengthened, but the ferrite grains become coarse, so the toughness decreases significantly. Therefore, the silicon content is set to 0.01 to 0.35%, and preferably 0.02 to 0.30%.

[0047] [Mn: 1.30~2.10%] Mn is an effective component for increasing the strength of the weld metal. If the Mn content is less than 1.30%, the strength will be low. On the other hand, if the Mn content exceeds 2.10%, the strength of the weld metal will be high and the toughness will be deteriorated. Therefore, the Mn content is set to 1.30 to 2.10%, and preferably 1.40 to 2.00%.

[0048] [Cu: 0.01~0.25%] Submerged arc welding wire is often copper-plated to stabilize wire feedability and current conduction. Therefore, when copper plating is applied, the wire contains a certain amount of Cu. On the other hand, if the Cu content is excessive, weld cracks are likely to occur, so the Cu content is set to 0.01 to 0.25%, preferably 0.05 to 0.20%.

[0049] [Ni:0.70~3.20%] Ni is an element intended to ensure the strength and toughness of the weld metal. If Ni is less than 0.70%, the strength and toughness of the weld metal decrease. On the other hand, if Ni exceeds 3.20%, the austenite grain size of the weld metal becomes coarse, decreasing the toughness. Therefore, Ni is set to 0.70 to 3.20%, and preferably 0.80 to 2.80%.

[0050] [Mo: 0.40~0.90%] Mo is an element intended to ensure the strength of the weld metal. If Mo is less than 0.40%, the strength of the weld metal will be low. On the other hand, if Mo exceeds 0.90%, the hardness of the wire will increase significantly, impairing wire drawability. Therefore, Mo is set to 0.40 to 0.90%, and preferably 0.45 to 0.80%.

[0051] [Total of one or both of V and Nb: 0.001 to 0.070%] V and Nb are effective in improving the strength of the weld metal, and in order to obtain this effect, the total content of one or two of these elements is set to 0.001% or more. On the other hand, excessive addition of these elements significantly increases the hardness of the wire and inhibits wiredrawability, so the total content of one or two of these elements is set to 0.070% or less, preferably 0.003 to 0.060%.

[0052] [P: 0.015% or less, S: 0.015% or less] Both P and S form compounds with low melting points and reduce toughness, so it is desirable to keep their contents as low as possible, but a content of 0.015% or less for each is permissible.

[0053] [Ceq (carbon equivalent): 0.40-0.80%] The carbon equivalent (Ceq) of the wire according to the present invention is expressed by the following formula (1). Ceq=C+Si / 24+Mn / 6+Ni / 40+Cr / 5+Mo / 4+V / 14...(1) In formula (1), C, Si, Mn, Ni, Cr, Mo, and V are the contents (mass%) of each element, and the content of an element that is not contained is 0 (zero).

[0054] The above Ceq must be in the range of 0.40 to 0.80% in order to ensure an appropriate strength for 780 MPa steel and to avoid deterioration of wire drawability due to excessive hardening. If Ceq is less than 0.40%, the target strength cannot be obtained. On the other hand, if Ceq exceeds 0.80%, the hardness of the wire becomes excessively high and the wire drawability deteriorates. Therefore, the Ceq of the wire is set to 0.40 to 0.80%, and preferably 0.45 to 0.72%.

[0055] [Optional composition of wire] In addition to the above composition, the welding wire according to the present invention may further contain, as necessary, one or more optional compositions selected from Cr: 0.01-0.10%, Ti: 0.001-0.050%, and Al: 0.001-0.050%.

[0056] [Cr: 0.01~0.10%] Cr has the effect of ensuring the yield and strength in the weld metal and stabilizing the toughness, and is contained as necessary in the present invention. When Cr is contained, the content is preferably 0.01% or more in order to obtain the above-mentioned effect of Cr, but since excessive addition significantly increases the hardness of the wire and inhibits the wiredrawability, the content is preferably 0.10% or less. More preferably, it is 0.02 to 0.08%.

[0057] [Ti: 0.001~0.050%] Although Ti has an effect of improving the toughness of the weld metal of 580 MPa class steel when contained at 0.001% or more, the effect of improving the toughness of the weld metal of 780 MPa class steel is relatively small, so that its addition is optional in the present invention. If Ti is added, 0.001% or more is preferable, but an excessive content increases the amount of solid-solubilized Ti in the weld metal and reduces the toughness, so 0.050% or less is preferable. More preferably, it is 0.003 to 0.030%.

[0058] [Al: 0.001~0.050%] Al is used as a deoxidizer as necessary, and is contained in the welding wire at 0.001% or more. When contained, it produces a compound with a low melting point and reduces toughness, but it is permissible if it is 0.050% or less, so 0.050% or less is preferable. It is more preferable that it is 0.001 to 0.030%.

[0059] [Remaining composition] The balance of the welding wire is composed of Fe and inevitable impurities, such as O (oxygen) and N. It is preferable that O is 0.004% or less and N is 0.008% or less.

[0060] [Wire diameter] Regarding the wire diameter, if the wire is less than 4.0 mm, the arc will be thin, it will be difficult to obtain a bead width, and the shape of the penetration bottom will be sharp, making defects such as slag inclusion more likely to occur. On the other hand, if the wire diameter exceeds 6.4 mm, the rigidity of the wire will be too high, placing too much strain on the wire feeder of the welding machine. Therefore, the wire diameter is preferably 4.0 to 6.4 mm.

[0061] [Welding method] [Heat input 100kJ / cm or more] The submerged arc welding method according to the present invention is highly efficient when performed with a heat input of 100 kJ / cm or more. This range of heat input is a heat input region that has not been considered in the prior art, and allows the effects of the present invention to be achieved. Here, the heat input refers to the heat input per pass, and in the case of multiple electrodes, it is the sum of the heat inputs of each electrode per pass. However, since an excessive heat input can cause problems such as excessive blowing up of molten slag, the heat input is preferably 300 kJ / cm or less.

[0062] [Multi-layer welding] For example, in the case of welding box column corner joints, when the base metal thickness exceeds the range that can be completed in one pass, the present invention preferably employs multi-layer welding with a heat input of 100 kJ / cm or more to ensure a weld metal with strength and toughness equivalent to that of the base metal. The interpass temperature is preferably 100 to 350°C. If the interpass temperature is less than 100°C, hydrogen cracking is likely to occur, and if it exceeds 350°C, problems such as insufficient strength and toughness of the welded portion are likely to occur.

[0063] [Base material thickness] The thickness of the base material is not particularly limited, but is preferably 20 to 150 mm.

[0064] [Group shape] Regarding the groove shape, the groove angle and root spacing are preferably as follows. If the groove angle is less than 25°, welding defects such as slag inclusion and insufficient fusion are likely to occur, and if it exceeds 50°, the number of welding passes increases and the construction time becomes excessive, so 25 to 50° is preferable. In addition, if the root spacing is more than 15 mm, insufficient penetration is likely to occur, so it is preferably 15 mm or less.

[0065] [Electrode arrangement] In the case of two electrodes, the following conditions are preferable for the electrode arrangement in the groove: The electrode spacing (spacing between the wire tips of the leading and trailing electrodes) is preferably 30 to 100 mm. If the electrode spacing is less than 30 mm, bead formation is likely to become unstable, and if it exceeds 100 mm, the molten pool is likely to become two pools.

[0066] The extension of the leading electrode is preferably 30 to 60 mm, and the extension of the trailing electrode is preferably 40 to 70 mm. If the extension of the leading electrode is less than 30 mm, the electrode tip is likely to melt, and if it exceeds 60 mm, the effect of deviation from the target position due to the wire bending tendency becomes large. Similarly, if the extension of the trailing electrode is less than 40 mm, the electrode tip is likely to melt, and if it exceeds 70 mm, the effect of deviation from the target position due to the wire bending tendency becomes large.

[0067] Furthermore, with regard to the inclination angles of the electrodes, it is preferable to set the leading electrode to a receding angle of 3 to 15° and the trailing electrode to a forward angle of 3 to 20°, because this provides deep penetration and a weld with a good appearance.

[0068] [Target diffusible hydrogen content, strength and toughness] The present invention relates to a weld metal of a submerged arc welded joint having a heat input of 100 kJ / cm or more and a base material having a tensile strength of 780 MPa or more, and a diffusible hydrogen content of 5.00 mL / 100 g or less, a tensile strength of 780 MPa or more, and V E0℃: The goal is to secure 100J or more.

[0069] The reason for this is that if the amount of diffusible hydrogen in the weld metal is 5.00 mL / 100 g or less, defects such as cracks in the HAZ are unlikely to occur. Preferably, it is 4.00 mL / 100 g or less. In addition, if the tensile strength of the weld metal is 780 MPa or more and V This is because the strength and toughness required for architectural structures can be ensured if E0°C is 100 J or more. Preferably, the 0.2% proof stress is 630 to 780 MPa and the tensile strength is 780 to 980 MPa. EXAMPLES

[0070] The present invention will now be described in more detail with reference to examples.

[0071] Baked fluxes with various chemical compositions shown in Table 1 were prototyped and combined with the seven types of solid wires shown in Table 2. Welding tests were conducted using two-electrode submerged arc welding on a 780 MPa-class high-tensile steel plate with a thickness of 50 mm and a chemical composition shown in Table 3 as the base material.

[0072] The fluxes F11, F13, and F15 shown in Table 1 are fluxes with the same component systems as the fluxes F1, F3, and F5 above them, to which one or a total of two or more of Si, Mn, Al, Ti, and Mg have been added within the range of the present invention.

[0073] In this welding test, corner welding of a box column as shown in Figure 1 was assumed, one of the two base materials 1 was a flange plate 1F and the other was a web plate 1W, and a groove shape with a groove angle θ of 42° and root spacing R of 2 mm was machined on these, and welding was performed with a backing metal 2 in place. The welding conditions were as shown in Table 4, and four passes of welding were performed to produce a welded joint.

[0074] Fig. 2 shows the electrode arrangement of two electrodes in the groove. The electrode interval D, which is the distance between the center positions of the tips of the welding wires 5 of the leading electrode (leading electrode E1) and the trailing electrode (trailing electrode E2), was set to 60 mm, the extension X1 of the leading electrode E1 was set to 40 mm, and the extension X2 of the trailing electrode E2 was set to 50 mm. In addition, the inclination angles δ of the electrodes were set to a 5° receding angle for the leading electrode E1 and a 10° advance angle for the trailing electrode E2.

[0075] A schematic cross section of the obtained welded joint is shown in Fig. 3. The weld metal 4 was welded in four passes. The preheat temperature for the first pass was 100°C, and the interpass temperatures for the second and subsequent passes were 150°C.

[0076] The combination of the sintered flux in Table 1 and the welding wire in Table 2 is as shown in Table 5. The sintered flux shown in Table 1 was prepared by blending and mixing various mineral raw materials, granulating them with water glass as a binder, sintering them at 450-500°C for 1 hour, and then sizing the particles so that they were 70% or more in the particle size range of 12-200 mesh (12x200 mesh). The welding wire 5 shown in Table 2 was drawn to a wire diameter of 4.8 mm before use.

[0077] The welding workability was examined by examining the arc stability during multi-layer welding, slag removability, and bead appearance and shape. After that, to check for the occurrence of cracks in the obtained weld metal 4, a vertical ultrasonic test was performed using a vertical flaw detector 3 from the flange plate 1F as shown in Figure 3. For those that showed an echo height of 20% or more, defects in the weld metal 4 were observed by macro cross-sectional inspection, and the causes of the defects, such as slag entrapment, were confirmed.

[0078] In addition, the strength test of the weld metal 4 was performed at the center 4C of the weld metal at a distance L T A 10 mm tensile test piece of JIS Z 3111 No. A1 test piece was taken from position 10, and the test was carried out.

[0079] As shown in Fig. 5, the impact test of the weld metal 4 was performed at the center 4C of the weld metal at a distance L SJIS Z 3128 standard test pieces were taken from the Charpy test piece sampling position 11 at 2 mm from the specimen, and the test was carried out. The tensile strength was evaluated as good when the 0.2% proof stress was 630-780 MPa and the tensile strength was 780-980 MPa. The toughness was evaluated by performing an impact test at 0°C and measuring the absorbed energy ( V E0℃) was considered good when it was 100J or more as the average value of three pieces.

[0080] The amount of diffusible hydrogen in the weld metal 4 was measured in accordance with JIS Z 3118. The amount of diffusible hydrogen in the weld metal 4 was determined to be good when it was 4.00 mL / 100 g or less. The results of these investigations are summarized in Table 5.

[0081] In Table 5, Examples 1 to 9 of the present invention were carried out using fluxes within the range of the present invention in combination with the respective welding wires. Examples 10, 11, and 12 of the present invention were carried out using fluxes F13, F15, and F11 in combination with welding wires W2, W3, and W7, respectively, for comparison with Examples 3, 5, and 6. Comparative Examples 1 to 5 of the present invention were carried out using fluxes outside the range of the present invention in combination with the respective welding wires in the same manner.

[0082] In Examples 1 to 9, the 0.2% proof stress and tensile strength of the weld metal were appropriate for all welding wires, and excellent toughness was obtained. In addition, the amount of diffusible hydrogen was low, the arc was stable, the slag removability, and the bead appearance and shape were good and defect-free, which were very satisfactory results. Among them, Examples 1 to 5, in which the welding wire satisfied the conditions of the present invention, obtained more sufficient strength and toughness than Examples 6 and 7 to 9.

[0083] In Examples 10 to 12, the 0.2% proof stress and tensile strength of the weld metal were appropriate for all welding wires, and excellent toughness was obtained. The amount of diffusible hydrogen was also low, the arc was stable, the slag removability and the bead appearance and shape were good and defect-free, and the results were extremely satisfactory. In particular, the toughness of the weld metal of Examples 10, 11 and 12 was improved by 20 J or more compared to Examples 3, 5 and 6, respectively.

[0084] In contrast to the above invention examples, in Comparative Example 1, flux symbol F6 is outside the scope of the present invention, while welding wire symbol W2 is within the scope of the present invention. Flux symbol F6 contains a lot of MgO, so protrusions are generated on the bead surface, resulting in poor bead appearance and slag inclusion. In addition, the total of the CO2 equivalent values ​​of one or two of CaCO3 and MgCO3 is low, so the amount of diffusible hydrogen in the weld metal is high. Furthermore, the arc is unstable because of the high CaF2 content. In addition, the Mo content is low, and the total of one or two of V and Nb is low, so the 0.2% proof stress of the weld metal is low.

[0085] In Comparative Example 2, the flux symbol F7 is outside the scope of the present invention, while the welding wire symbol W3 is within the scope of the present invention. The flux symbol F7 has a low SiO2 content, so the bead toe does not conform well, and the bead shape and slag removability are poor. In addition, the flux symbol F7 has a low MgO content, which affects the deterioration of slag removability, and the bead has a rough wavy shape and pockmarks, resulting in poor bead appearance. In addition, the total of the CO2 equivalent values ​​of one or two of CaCO3 and MgCO3 is high, which is one of the causes of pockmarks, and the amount of oxygen in the weld metal increases, decreasing toughness. In addition, the flux symbol F7 has a high Mo content and a high total of one or two of V and Nb, so the tensile strength of the weld metal is excessively high.

[0086] In Comparative Example 3, both the flux symbol F8 and the welding wire symbol W7 are outside the scope of the present invention. The flux symbol F8 had poor slag removability due to a small amount of CaO. In addition, the flux symbol F8 had a large amount of Al2O3, which resulted in a convex bead and a poor bead shape, which was one of the causes of poor slag removability. In addition, slag inclusion occurred in the weld metal. Furthermore, the total amount of Na2O and K2O was small, which made the arc unstable. On the other hand, the welding wire symbol W7 also had low amounts of C, Ni, Mo, and Ceq and low amounts of the total amount of one or two of V and Nb, which resulted in low 0.2% proof stress and tensile strength of the weld metal. Furthermore, the flux symbol F8 had a large amount of P and Ti, which resulted in low Charpy absorbed energy of the weld metal.

[0087] In Comparative Example 4, the flux code F9 is outside the scope of the present invention, while the welding wire code W2 is within the scope of the present invention. Flux code F9 contains a large amount of CaO, so the bead height is non-uniform and the bead shape and slag removability are poor. In addition, the total of the CO2 equivalent values ​​of one or both of CaCO3 and MgCO3 is small, so the amount of diffusible hydrogen in the weld metal is high. In addition, the Ni and Cr are large, so the tensile strength of the weld metal is excessively high. As the strength of the weld metal increases, the Charpy absorbed energy also becomes low.

[0088] In Comparative Example 5, both the flux symbol F10 and the welding wire symbol W7 are outside the scope of the present invention. The flux symbol F10 contains a large amount of SiO2, which results in poor slag removability, and an increase in the amount of oxygen in the weld metal, resulting in a low Charpy absorbed energy. In addition, the flux symbol F10 contains a small amount of CaF2, which results in a narrow bead width and a poor bead shape. On the other hand, the welding wire symbol W7 contains a small amount of C, Ni, Mo, and Ceq, and a small amount of one or two of V and Nb in total, resulting in a low 0.2% proof stress of the weld metal. In addition, the flux symbol F10 contains a large amount of P and Ti, which results in a low Charpy absorbed energy of the weld metal.

[0089] [Table 1]

[0090] [Table 2]

[0091] [Table 3]

[0092] [Table 4]

[0093] [Table 5] [Explanation of symbols]

[0094] 1 Base material 1F Flange plate 1W Web Board 2. Backing 3 Vertical flaw detector 4. Weld metal 4C Weld metal center 5 Welding Wire 10 Tensile test specimen collection position 11 Charpy test piece location t (base material) plate thickness R Root Spacing θ Bevel angle δ (electrode) inclination angle D Electrode spacing E1 leading pole, E2 trailing pole X1 Leading pole extension, X2 Trailing pole extension L T Distance from the plate surface to the location of the tensile test specimen at the center of the weld metal 4C L S Distance from the plate surface to the location of Charpy test specimen at the center of the weld metal 4C

Claims

1. A sinterable flux for submerged arc welding of high tensile steel, comprising: The chemical composition of the sintered flux is, in mass%, Yes 2 :15~25%, CaO: 3-15%, MgO: 25-45%, <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> :5~220%、 CaF 2 :5~20%、 Na 2 O and K 2 Total of one or two types of O: 0.5 to 10.0%, CaCO 3 and MgCO 3 One or two of the following CO 2 Total conversion value: 3-8% Ni: 3.00-7.20%, Cr: 0.90-2.40%, Mo: 0.50-1.30%, Sum of one or both of V and Nb: 0.080 to 0.220% Contains The balance is composed of Fe from iron alloys and inevitable impurities. A baked flux for submerged arc welding of high tensile steels, characterized in that

2. In addition to the chemical composition of the sintered flux, the composition further comprises, in mass %, One or more selected from the group consisting of Si, Mn, Al, Ti and Mg: 0.6 to 3.0% in total 2. The sinterable flux for submerged arc welding of high tensile steel according to claim 1.

3. 3. The sinterable flux for submerged arc welding of high tensile steel according to claim 1, wherein the high tensile steel has a tensile strength of 780 MPa or more.

4. A method for submerged arc welding of high tensile steel, comprising the steps of: combining the sintered flux according to claim 1 or 2 with a welding wire; The chemical composition of the welding wire is, in mass%, C: 0.05-0.12%, Si: 0.01-0.35%, Mn: 1.30 to 2.10%, Cu: 0.01-0.25%, Ni: 0.70-3.20%, Mo: 0.40-0.90%, Sum of one or both of V and Nb: 0.001 to 0.070%, P: 0.015% or less, S: 0.015% or less; Ceq represented by the following formula (1) is 0.40 to 0.80%, The balance is Fe and unavoidable impurities. A method for submerged arc welding of high tensile steel. Ceq=C+Si / 24+Mn / 6+Ni / 40+Cr / 5+Mo / 4+V / 14...(1) In formula (1), C, Si, Mn, Ni, Cr, Mo, and V are the contents (mass%) of each element, and the content of an element that is not contained is 0 (zero).

5. In addition to the chemical composition of the welding wire, further, in mass%, Contains one or more selected from the group consisting of Cr: 0.01-0.10%, Ti: 0.001-0.050%, and Al: 0.001-0.050%.

5. The method for submerged arc welding of high tensile steel according to claim 4.

6. 5. The method for submerged arc welding of high tensile steel according to claim 4, wherein the high tensile steel has a tensile strength of 780 MPa or more.

7. 6. The method for submerged arc welding of high tensile steel according to claim 5, wherein the high tensile steel has a tensile strength of 780 MPa or more.

8. 5. The method for submerged arc welding of high tensile steel according to claim 4, characterized in that the welding heat input is 100 kJ / cm or more.

9. 6. The method for submerged arc welding of high tensile steel according to claim 5, wherein the welding heat input is 100 kJ / cm or more.

10. 5. The method for submerged arc welding of high tensile steel according to claim 4, characterized in that the welding is performed by multi-pass welding.

11. 6. The method for submerged arc welding of high tensile steel according to claim 5, characterized in that the welding is performed by multi-pass welding.

Citation Information

Patent Citations

  • Welding method for rotor welding compensation

    JP1986249699A

  • Submerged arc welding method for high-strength cr-mo steel

    JP1990084293A

  • Wire and bonded flux for submerged arc welding of 780mpa or 960mpa steel

    JP1995303991A

  • Two electrode type heavy heat input submerged arc welding method

    JP2005271045A

  • Submerged arc weld metal of high tensile strength steel

    JP2007260696A